We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
57
1
avatar+153 

Find the polynomial p(x), with real coefficients, such that p(2) = 5 and p(x) p(y) = p(x) + p(y) + p(xy) - 2 for all real numbers x and y.

 Nov 21, 2019
 #1
avatar+23542 
+2

Find the polynomial \(p(x)\), with real coefficients,
such that \(p(2) = 5\) and \(p(x) p(y) = p(x) + p(y) + p(xy) - 2\) for all real numbers \(x\) and \(y\).

 

\(\begin{array}{|lrcll|} \hline & \mathbf{ p(x) p(y)} &=& \mathbf{ p(x) + p(y) + p(xy) - 2 } \\\\ x=1,\ y=2: & p(1) p(2) &=& p(1) + p(2) + p(1*2) - 2 \quad | \quad \mathbf{p(2) = 5} \\ & p(1) *5 &=& p(1) + 5 + 5 - 2 \\ & 5p(1) &=& p(1) + 8 \\ & 4p(1) &=& 8 \\ & p(1) &=& \dfrac{8}{4} \\ & \mathbf{p(1)} &=& \mathbf{2} \\\\ x=0,\ y=2: & p(0) p(2) &=& p(0) + p(2) + p(0*2) - 2 \quad | \quad \mathbf{p(2) = 5} \\ & p(0) *5 &=& p(0) + 5 + p(0) - 2 \\ & 3p(0) &=& 3 \quad | \quad :3 \\ & \mathbf{p(0)} &=& \mathbf{1} \\ \hline \end{array}\)

 

\(\begin{array}{|lrcll|} \hline & p(0) &=& 1 \\ & p(1) &=& 2 \\ & p(2) &=& 5 \\ \hline & p(x) &=& ax^2+bx+c \\ p(0)=1: & 1 &=& a*0^2+b*0 +c \\ & \mathbf{c} &=& \mathbf{1} \\\\ p(1)=2: & 2 &=& a*1^2+b*1 +c \quad | \quad c=1 \\ & 2 &=& a+b+1 \\ & \mathbf{a+b} &=& \mathbf{1} \\\\ & \mathbf{ b} &=& \mathbf{1-a} \\\\ p(2)=5: & 5 &=& a*2^2+b*2 +c \\ & 5 &=& 4a+2b +c \quad | \quad c=1 \\ & 5 &=& 4a+2b + 1 \\ & 4 &=& 4a+2b \quad | \quad :2 \\ & 2a+b &=& 2 \quad | \quad b=1-a \\ & 2a+1-a &=& 2 \\ & \mathbf{ a} &=& \mathbf{1 } \\\\ & \mathbf{ b} &=& \mathbf{1-a} \quad | \quad a = 1 \\ & b &=& 1-1 \\ & \mathbf{b} &=& \mathbf{0} \\ \hline & p(x) &=& ax^2+bx+c \quad | \quad a=1,\ b=0,\ c=1 \\ & \mathbf{p(x)} &=& \mathbf{x^2+1} \\ \hline \end{array}\)

 

check:

\(\begin{array}{|rcll|} \hline \mathbf{ p(x) p(y)} &=& \mathbf{ p(x) + p(y) + p(xy) - 2 } \\\\ (x^2+1)(y^2+1) &=& (x^2+1) + (y^2+1) + \left((xy)^2+1\right) - 2 \\ x^2y^2+x^2+y^2+1 &=& x^2+1 + y^2+1 + x^2y^2+1 - 2 \\ x^2y^2+x^2+y^2+1 &=& x^2y^2+ x^2+y^2 + 1 +1 +1 - 2 \\ x^2y^2+x^2+y^2+1 &=& x^2y^2+ x^2+y^2 + 3 - 2 \\ x^2y^2+x^2+y^2+1 &=& x^2y^2+ x^2+y^2 + 1\ \checkmark \\ \hline \end{array}\)

 

laugh

 Nov 21, 2019

31 Online Users

avatar
avatar